1999
DOI: 10.1186/1297-9686-31-1-61
|View full text |Cite
|
Sign up to set email alerts
|

Selection for reduced muscle glycolytic potential in Large White pigs. II. Correlated responses in meat quality and muscle compositional traits

Abstract: -A selection experiment was conducted over six generations in a purebred French Large White population presumably free of the HAL" and RN-alleles. Two lines were taken from the same base population and were contemporarily bred: one control line (C) and one line (S) (-0, 42 ! 0, 12

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
10
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 22 publications
5
10
0
2
Order By: Relevance
“…Estimates were 0.35 on average, superior to the average literature value of 0.21 reported in Sellier (1998). They were also greater than the estimates reported by Larzul et al (1999a) and van Wijk et al (2005), but were close to the value reported by Nguyen Table 3. Models of analyses, significance, and total variation explained by fixed-effect terms (R 2 ) GS, BF, and AF = gluteus superficialis, biceps femoris, and adductor femoris muscles, respectively.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Estimates were 0.35 on average, superior to the average literature value of 0.21 reported in Sellier (1998). They were also greater than the estimates reported by Larzul et al (1999a) and van Wijk et al (2005), but were close to the value reported by Nguyen Table 3. Models of analyses, significance, and total variation explained by fixed-effect terms (R 2 ) GS, BF, and AF = gluteus superficialis, biceps femoris, and adductor femoris muscles, respectively.…”
Section: Discussionsupporting
confidence: 85%
“…The heritability estimates for reflectance are within the range found in the literature (Lo et al, 1992;de Vries et al, 1994;Knapp et al, 1997;Sellier, 1998). Among meat quality traits, heritability values for WHC_GS and WHC_BF were in agreement with those reported by Tribout et al (1996) and Sonesson et al (1998), but less than the estimates presented by the most recent literature reviews (Larzul et al, 1999a;Hermesch et al, 2000a). With estimates ranging from 2 to 9% of the phenotypic variance, common litter effects fell in the range of values reported in the literature.…”
supporting
confidence: 86%
“…Recent results also highlighted a negative relationship between chicken breast muscle glycolytic potential and carcass leanness (Berri et al, 2005). Therefore, in chickens, selection for growth and leanness would lead to lower muscle glycogen content, whereas in pigs, increasing lean meat content led to greater muscle glycogen content (Larzul et al, 1999). Furthermore, the negative relationships found in chickens between the growth and leanness and the muscle glycogen content could explain the lack of difference in muscle glycogen between chicken males and females because females exhibited greater breast yield and greater fatness than males.…”
Section: Muscle Fiber Cross-sectional Area and Meat Quality Traitsmentioning
confidence: 99%
“…Differences in muscle fiber characteristics are influence by various factors including breed (Ryu et al, 2008), selection (Larzul et al, 1999), gender (Ozawa et al 2000), hormone (Rehfeldt et al, 2004), growth performance (Kim, et al, 2013), diet (Jeong et al 2012) and muscle location (Hwang et al 2010).…”
Section: Introductionmentioning
confidence: 99%